Plane wave, pattern subtraction, range compensation. - Leatherwood, D.A (IEEE Transactions on antennas and propagation)
Plane wave, pattern subtraction (PWPS) range compensation improves the performance of far field and compact, antenna pattern measurement systems by compensating errors introduced by antenna measurement facility (range) imperfections. The range-field model consists of a plane wave that represents an ideal range field plus a selectable number of plane waves representing range field imperfections. The error patterns introduced by the undesired range-field plane waves are estimated and subtracted from the measured pattern to produce a compensated pattern. This compensated pattern is used to obtain an improved estimate of the error patterns. This iterative procedure is continued until the compensation algorithm converges. The antenna measurement range field is measured on the surface of a sphere enclosing the test zone, and a plane-wave model of this range field is constructed